Biomedical stent as well as preparation method, use method and application thereof
By using the combination of shape memory and active particles, combined with dichloromethane solvents and 3D printing technology, to prepare biomedical brackets with shaped memory and self -adhesion function, solve the problem of insufficient preparation and performance in existing technologies, realize the realization, and achieve realization, realize the realization The precision preparation of brackets and various biological effects.
Patent Information
- Application Number
- CN202411299606.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-24
AI Technical Summary
The existing shape memory biomedical scaffolds have shortcomings in the preparation process and performance, making it difficult to achieve precision preparation and improve processability and mechanical properties, and it is difficult to have the effects of anti-tumor and promoting bone function.
A biomedical stent composed of 96.0%-99.5% shape memory polyurethane and 0.5%-4% active particles (such as manganese dioxide, nano-magnesium oxide, etc.) is prepared through dichloromethane solvent dissolution and 3D printing technology to achieve Shape memory and self-adhesive functions of the stent.
It achieves precise preparation of the scaffold, improves the processability and mechanical properties, and has biological effects such as removing ROS in the body, photothermal anti-tumor, and promoting bone regeneration, and is suitable for bone defect repair and other tissue repair scenarios.
Smart Images

Figure CN119345460A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomedical materials, and in particular to a biomedical stent and a preparation method, a use method and an application thereof. Background Art
[0002] The repair of large-scale bone defects caused by fractures, trauma, etc. has always been one of the most concerned issues in the field of public health. For example, the bone defect caused by osteosarcoma resection surgery is a thorny problem in the clinical repair of bone defects due to its large area, irregular shape, and residual tumor cells leading to tumor recurrence. At present, the clinical treatment plan for osteosarcoma includes preoperative adjuvant chemotherapy, tumor surgical resection, and postoperative adjuvant chemotherapy. The purpose is to retain the patient's limb function on the basis of maximal tumor resection and improve the postoperative survival rate. However, the residual border tumor tissue and potential micro-lesions after surgery will lead to a high risk of recurrence and metastasis. Once this occurs, the patient's 5-year postoperative survival rate is less than 20%. In addition, the large-area irregular bone defect caused by extensive tumor resection surgery and the low immunity caused by subsequent radiotherapy / chemotherapy seriously affect the healing and regeneration of bone defects after osteosarcoma surgery, which brings huge challenges to the retention and reconstruction of patients' limb function, and will lead to a very high rate of disability and deformity, seriously affecting the patient's postoperative quality of life.
[0003] At present, traditional bone repair materials mainly include autologous bone, allogeneic bone, bioceramics, etc., but these technologies or materials have shortcomings such as insufficient donors, secondary damage to patients, large trauma, high bleeding, low biological activity, and insufficient mechanical properties. For the repair of refractory bone defects after osteosarcoma surgery, traditional bone repair materials are difficult to match the irregular defect shape during clinical operation, and cannot completely cover the edge of the defect during filling, affecting the fixation effect, and it is difficult to have both anti-tumor and osteogenic functions.
[0004] As a type of stimulus-responsive smart material, shape memory polymers (SMPs) have been used in bone defect repair research. In addition to achieving minimally invasive surgery and biocompatibility, they can also achieve self-fixation function to tightly fill irregular defect sites after implantation and enhance the interaction between materials and tissue interfaces. Currently, shape memory polyurethane (SMPU) is synthesized by a one-step or two-step method, and most of them are simple or rough linear structures. Traditional preparation techniques often fail to achieve satisfactory results for the personalized structure of bone repair devices and the design optimization of macro / micro porous structures, which greatly limits the further clinical application of shape memory materials. Summary of the invention
[0005] In view of the shortcomings of the existing preparation process and performance of shape memory biomedical scaffolds, the technical problem to be solved by the present invention is to provide a new biomedical scaffold with shape memory and self-adhesion functions and its 3D printing method, so as to achieve the precise preparation of shape memory biomedical scaffolds and improve the processability and physical and chemical properties such as mechanics and memory, so as to further achieve biological effects such as removal of ROS in the body, photothermal anti-tumor, and promotion of bone regeneration. The manufacturing method of the new biomedical scaffold is relatively simple, easy to implement industrially, and has wide applicability. Based on this, the present invention provides a biomedical scaffold and its preparation method, use method and application.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] The invention provides a biomedical stent, which comprises the following raw material components in percentage by mass: 96.0%-99.5% of shape memory polyurethane and 0.5%-4% of active particles; wherein the active particles comprise one or more of manganese dioxide, nano-magnesium oxide, ferroferric oxide and magnesium metal.
[0008] Furthermore, the biomedical stent includes the following raw material components by mass percentage: 96.0% of shape memory polyurethane and 4% of active particles.
[0009] The invention also provides a preparation method of a biomedical scaffold, which comprises the following steps: preparing shape memory polyurethane, stirring and dissolving the shape memory polyurethane in a sealed environment at a temperature of 70-75°C with dichloromethane as a solvent; adding active particles to obtain a mixed solution after the shape memory polyurethane is completely dissolved and cooled to room temperature; stirring in an open environment at a temperature of 70-75°C to volatilize the dichloromethane until the mixed solution is a non-flowing uniform colloid, thereby obtaining a shape memory polyurethane / active particle printing liquid; printing with the shape memory polyurethane / active particle printing liquid, and after printing is completed, naturally volatilizing the dichloromethane to obtain a shape memory polyurethane / active particle composite bone repair scaffold with shape memory and self-adhesion functions, namely the biomedical scaffold.
[0010] Furthermore, the volume ratio of the shape memory polyurethane to dichloromethane is 1:7-1:10, preferably 1:9.
[0011] Furthermore, in the step of preparing the shape memory polyurethane and stirring and dissolving the shape memory polyurethane in a sealed environment at a temperature of 70-75° C. using dichloromethane as a solvent, the stirring and dissolving is specifically dissolved by magnetic stirring, and the stirring time is 0.5-2 hours, preferably 1.5 hours.
[0012] Furthermore, after the shape memory polyurethane is completely dissolved and cooled to room temperature, active particles are added to obtain a mixed solution step, which specifically includes cooling at room temperature for 1 hour until it is completely cooled to room temperature, and then adding active particles in an open condition.
[0013] Further, in the step of obtaining the shape memory polyurethane / active particle printing liquid, stirring under open conditions at a temperature of 70-75° C. to evaporate the dichloromethane until the mixed solution becomes a non-flowing uniform colloid, specifically includes evaporating the mixed solution to 1 / 9 of its original volume.
[0014] Furthermore, the operating parameters for printing with the shape memory polyurethane / active particle printing liquid are as follows: printing the shape memory polyurethane / active particle printing liquid at 25-28° C., 0.8 bar-1.1 bar extrusion, and a printing speed of 5-10 mm / s.
[0015] The present invention also provides a method for using a biomedical stent, which comprises the following steps: placing the biomedical stent under normal temperature conditions for deformation and compression treatment, and after the shape is fixed at normal temperature, implanting the stent into a tissue site according to needs; heating the stent with hot water at 45-60°C or a wavelength of 808nm and a power density range of P=0.5w / cm 2 -2w / cm 2 The biomedical scaffold is restored to its original state by near-infrared light irradiation, so as to fix the supporting tissue and promote tissue regeneration and repair; or, the biomedical scaffold is placed at room temperature, and scaffolds with different pore sizes, different active ingredients and different contents are spliced together according to needs to customize the required shape, and placed in a heating environment of 45-60°C or a wavelength of 808nm, and a power density range of P=0.5w / cm 2 -2 w / cm 2 Under near-infrared light irradiation, the brackets are spliced into a whole due to their self-adhesion function.
[0016] The present invention further provides the use of the above-mentioned biomedical stent in the field of treating fractures and trauma.
[0017] Compared with the prior art, the technical solution provided by the present invention has at least the following advantages:
[0018] (1) The present invention proposes a technical solution combining shape memory polymers with bioactive metals. By superimposing the respective properties of shape memory polyurethane and manganese dioxide, a composite bone repair scaffold is constructed that can fit tightly to the defect site, provide mechanical stimulation, and at the same time has bioactivity, making it more capable of real service.
[0019] (2) The performance of shape memory polymers is easily affected by temperature during low-temperature or high-temperature 3D printing, and there is currently no effective and rapid 3D printing preparation method. The present invention uses dichloromethane solvent to dissolve shape memory polyurethane and perform room temperature molding to prepare a 3D printed intelligent biomedical scaffold containing active ingredients in a simple and rapid manner, and construct its uniform porous structure to achieve multiple biological functions.
[0020] (3) The scaffold provided by the present invention has excellent self-adhesion function, and can freely splice together scaffolds with different pore sizes, different active ingredients and different contents. In the face of complex osteosarcoma defect repair and regeneration and other tissue repair scenarios, it can achieve truly personalized customized repair. Compared with integrated 3D printing, it has simpler, more convenient and faster operation to achieve complex biological and material functions. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] One or more embodiments are exemplarily described by pictures in the corresponding drawings, and these exemplifications do not constitute limitations on the embodiments. Unless otherwise stated, the pictures in the drawings do not constitute proportional limitations.
[0022] Figure 1 The appearance of the stents of Examples 1-4 of the present invention and the comparative example;
[0023] Figure 2 It is a comparison of the surface morphology and the chlorine element scan;
[0024] Figure 3 is the light and heat performance of Examples 1-4 of the present invention and the comparative example;
[0025] Figure 4 1 is the stress-strain curve of Examples 1 to 4 of the present invention and the comparative example;
[0026] Figure 5 This is the shape recovery process of Example 4 of the present invention;
[0027] Figure 6 is the splicing performance of Example 4 of the present invention and the comparative example bracket;
[0028] Figure 7 It is the cell compatibility of Examples 1-4 of the present invention and the comparative example. DETAILED DESCRIPTION
[0029] The inventors have found that there are currently porous scaffolds for bone repair with photothermal properties based on shape memory polyurethane composite materials using advanced low-temperature 3D printing technology. For example, the prior art discloses a method for preparing a porous scaffold with shape memory function, which uses benzoyl peroxide as a cross-linking initiator, propylene alcohol as a plasticizer, and polycaprolactone diol as a matrix material to prepare a porous scaffold. However, its melting point is about 57°C, and its heat resistance and mechanical processing properties are not good, and its shape memory performance is only 20%. Due to the unique temperature response performance of shape memory polyurethane materials based on polycaprolactone diol, conventional low-temperature deposition and high-temperature deposition will have a great impact on its shape memory recovery performance and mechanical properties. Therefore, the development of room temperature 3D printing technology has a good improvement in the controllable preparation of shape memory polyurethane biomedical scaffolds. The solvent used for room temperature printing needs to have good solubility in polyurethane, rapid volatility, and relatively low biological toxicity. The prior art also discloses a room temperature shape memory scaffold, which uses chloroform as a solvent and then removes the solvent under a vacuum environment at 60°C. However, the nozzle temperature during the printing process was 160°C, the printing height was only 5mm, and the mechanical properties were not ideal. On the other hand, the active ingredients of the implant material play an important role in inhibiting the in situ regeneration of osteosarcoma and promoting osteogenesis. Manganese dioxide nanoparticles have excellent biological properties, such as promoting bone regeneration, promoting angiogenesis, and having photothermal effects. Other studies have found that MnO2 can eliminate H2O2 in the joints and produce oxygen, and continuously release FAPi to regulate immune responses and bone formation. It can effectively reduce intracellular ROS, guide macrophages to M2 polarization, and relieve inflammation.
[0030] In summary, for shape memory active scaffolds in biomedicine, especially in the field of bone repair, appropriate 3D printing technology and active ingredients should be combined to improve the mechanical and biological properties of the materials, thereby achieving biological functions such as supporting defective tissues, promoting tissue regeneration and repair, etc.
[0031] Based on this, the present invention provides a 3D printing technology of polyurethane with shape memory and self-adhesive functions and its composite active bracket: by using the easy volatilization of dichloromethane, the pressure in the container is increased, so that the shape memory polyurethane is very uniformly and stably dissolved and the activity can be evenly dispersed and mixed. This type of shape memory material is 3D printed by volatilization deposition at room temperature, and the printing structure such as pore size and porosity is further designed to achieve better shape memory performance and mechanical properties. At the same time, the present invention can heat multiple brackets in a variety of ways to assemble them into a specific shape for use, and has strong stability.
[0032] The present invention is aimed at the application in the field of biomedical material technology and provides a biomedical stent with shape memory and self-adhesion functions and a preparation method and a use method thereof.
[0033] The present invention is described in detail below with reference to the embodiments.
[0034] (I) The embodiment of the present invention provides a shape memory polyurethane (SMPU) and a scaffold of composite active particles thereof, specifically taking composite active manganese dioxide particles (MnO2) as an example. The biomedical scaffold includes the following raw material components in mass percentage:
[0035] SMPU 96.0%-99.5%;
[0036] MnO2 0.5%-4%;
[0037] (II) Preparation of SMPU / MnO2 composite bone repair scaffold
[0038] a) Cut the synthesized SMPU into small pieces and dissolve them in dichloromethane (preferably in a volume ratio of 1:9) in a sealed glass bottle under magnetic stirring at 70-75°C for one hour;
[0039] b) After SMPU is completely dissolved, prevent the boiling dichloromethane solution from spraying out, cool at room temperature for 1 hour, and open the bottle cap after it is completely cooled to room temperature. Add MnO2 particles (preferably the mass ratio of SMPU: MnO2 = 96:4);
[0040] c) stirring at 70-75° C. (preferably 73° C.) in an open environment to evaporate the dichloromethane solvent;
[0041] d) After evaporating to 1 / 9 of the original volume, the solution has no fluidity and is a non-flowing uniform colloid, which is then loaded into the printing barrel;
[0042] e) printing the SMPU / MnO2 printing liquid at 25-28°C (preferably 26°C), 0.8 bar-1.1 bar extrusion pressure (preferably 0.9 bar); and printing at a printing speed of 5-10 mm / s (preferably 8 mm / s);
[0043] f) After printing is completed, the dichloromethane is naturally evaporated in a fume hood to obtain a SMPU / MnO2 composite bone repair scaffold with shape memory and self-adhesion functions.
[0044] (III) Based on the premise of providing the biomedical stent, the present invention also provides a method for using the stent due to the shape memory and self-adhesion functions of the stent, which at least includes the following steps:
[0045] 1. Place the stent under normal temperature conditions for deformation and compression treatment. The stent can be fixed in shape at room temperature, and then implanted into the tissue site according to needs. The stent can be placed under corresponding temperatures such as hot water (45-60°C), near-infrared light irradiation (wavelength 808nm, power density range P = 0.5w / cm 2 -2 w / cm 2 , preferably 1w / cm 2 ), gradually returning to the original state of the scaffold, further fixing the supporting tissue and promoting tissue regeneration and repair.
[0046] 2. Place the stent at room temperature, splice together stents with different pore sizes, different active ingredients and different contents to customize the shape according to the needs, and place it in a heated environment (45-60℃, preferably 60℃) or a wavelength of 808nm, with a power density range of P = 0.5w / cm 2 -2 w / cm 2 Under near-infrared light irradiation, the stent can be firmly spliced into a whole due to its self-adhesion function, and has good stability, mechanical strength and shape memory performance. The shape memory process of step 1 can also be achieved.
[0047] In the SMPU / MnO2 biomedical scaffold embodiment, the mass fraction of MnO2 (relative to SMPU) is 0.5%, 1%, 2%, and 4% in the embodiment. In the printing liquid of the SMPU / MnO2 biomedical scaffold comparative example and the embodiment, the solvent is dichloromethane, and the volume ratio is 9:1. The raw materials and their amounts used in Examples 1-4 of the present invention and the comparative example are shown in the table below.
[0048] Table 1 Raw materials and their dosages used in Examples 1-4 of the present invention and Comparative Examples
[0049] Sample No. SMPU(g) <![CDATA[MnO2(g)]]> Dichloromethane (mL) Comparative Example S-0 10 0 90 Example 1 S-1 10 0.05 90 Example 2 S-2 10 0.10 90 Example 3 S-3 10 0.20 90 Example 4 S-4 10 0.40 90
[0050] Preparation of comparative example scaffold:
[0051] a) Cut the synthesized SMPU into small pieces, weigh 10 g, and dissolve it in 90 mL of dichloromethane in a sealed glass bottle at 70-75°C with magnetic stirring for one hour;
[0052] b) After SMPU is completely dissolved, prevent the boiling dichloromethane solution from spraying out, cool it at room temperature for 1 hour, and open the bottle cap after it is completely cooled to room temperature;
[0053] c) stirring at 70-75° C. (preferably 73° C.) in an open environment to evaporate the dichloromethane solvent;
[0054] d) Evaporate to 10-15mL, the solution has no fluidity, and is a non-flowing uniform colloid, then load it into the printing cylinder;
[0055] e) printing the SMPU printing liquid at 25-28° C. (preferably 26° C.), 0.8 bar-1.1 bar extrusion pressure (preferably 0.9 bar); and printing at a printing speed of 5-10 mm / s (preferably 8 mm / s);
[0056] f) After printing is completed, the dichloromethane is naturally evaporated in a fume hood to obtain an SMPU composite bone repair scaffold with shape memory and self-adhesion functions.
[0057] Specific preparation steps of the scaffolds of Examples 1-4:
[0058] a) Cut the synthesized SMPU into small pieces, weigh 10 g, and dissolve it in 90 mL of dichloromethane in a sealed glass bottle at 70-75°C with magnetic stirring for one hour;
[0059] b) After SMPU is completely dissolved, prevent the boiling dichloromethane solution from spraying out, cool at room temperature for 1 hour, and open the bottle cap after it is completely cooled to room temperature. Add MnO2 particles (0.05g, 0.1g, 0.2g, 0.4g) respectively;
[0060] c) stirring at 70-75° C. (preferably 73° C.) in an open environment to evaporate the dichloromethane solvent;
[0061] d) After evaporation to 10-15mL, the solution has no fluidity and is a non-flowing uniform colloid, then it is loaded into the printing barrel
[0062] e) printing the SMPU / MnO2 printing liquid at 25-28°C (preferably 26°C), 0.8 bar-1.1 bar extrusion pressure (preferably 0.9 bar); and printing at a printing speed of 5-10 mm / s (preferably 8 mm / s);
[0063] f) After printing is completed, the dichloromethane is naturally evaporated in a fume hood to obtain a SMPU / MnO2 composite bone repair scaffold with shape memory and self-adhesion functions.
[0064] The appearance comparison of the brackets provided in Examples 1-4 of the present invention and the comparative example is shown in FIG. Figure 1 The embodiment and the comparative example both have uniform bionic porous structures, uniform pores and distinct lines, which indicates that the printing method has excellent controllability over materials. In addition, as the content of MnO2 increases, the color of the stent gradually deepens.
[0065] The surface morphology of the comparative stent and the chlorine element scan are shown in Figure 2. The natural volatilization of dichloromethane creates tiny pores that are conducive to cell growth. The chlorine content is as low as 0.07%, indicating that the influence of dichloromethane solvent can be almost completely removed by natural volatilization, which is conducive to ensuring that the scaffold has good mechanical strength and biosafety.
[0066] The photothermal effects of the brackets provided in Examples 1-4 of the present invention and the comparative example are shown in FIG. Figure 3 Among them, the wavelength of near-infrared light is 808nm and the power density is 1.5w / cm 2 The comparative example has almost no temperature rise, while the temperature rise of Example 4 is relatively the fastest, the rise amplitude is also the largest, and the photothermal effect is the best.
[0067] The stress-strain curves of the stents provided in Examples 1-4 of the present invention and the comparative example are shown in Figure 4 Among them, the mechanical properties of the scaffold can be regulated by adjusting the added manganese dioxide content.
[0068] The shape recovery process of the stent in Example 4 of the present invention is shown in FIG. Figure 5 The stent was exposed to near-infrared light (wavelength 808nm, power density 1w / cm 2 ) has good shape recovery function under irradiation.
[0069] The splicing performance of the brackets provided in the comparative example and embodiment 4 is shown in Figure 6 By heating the surface of Example 4 at 60°C, the brackets are spliced at intervals to form a U-shaped hook through self-adhesion performance, which can withstand a weight that is 1200 times heavier than itself and has good splicing performance, stability and mechanical strength.
[0070] See Table 1 for a comparison of the cell compatibility of the scaffolds provided in Examples 1-4 of the present invention and the comparative example. Figure 7 Compared with the blank group cells (wherein, the blank group cells are normal cultured cells without any sample material added, i.e., the positive control) and the comparative example, Examples 1-4 have better cell compatibility.
[0071] The biomedical stent provided by the present invention has a variety of usage methods, two of which are generally used as follows:
[0072] 1. Place the stent under normal temperature conditions for deformation and compression treatment. The stent can be fixed in shape at room temperature, and then implanted into the tissue site according to needs. The stent can be placed under corresponding temperatures such as hot water (45-60°C), near-infrared light irradiation (wavelength 808nm, power density range P = 0.5w / cm 2 -2 w / cm 2 , preferably 1w / cm 2 ), gradually returning to the original state of the scaffold, further fixing the supporting tissue and promoting tissue regeneration and repair.
[0073] 2. Place the stent at room temperature, splice together stents with different pore sizes, different active ingredients and different contents to customize the shape according to the needs, and place them in a heated environment (45-60°C, preferably 60°C). Due to the self-adhesion function, the stent can be firmly spliced into a whole, and has good stability, mechanical strength and shape memory performance. The shape memory process of step 1 can also be achieved.
[0074] It can be seen that in the prior art, some shape memory polyurethanes have a high melting temperature, so high-temperature printing is difficult to extrude stably, cannot be quantified, and has poor performance; low-temperature 3D printing technology affects the crystallization of polyurethane materials, and the mechanical properties and shape recovery rate of the guide stent are reduced. Due to the inability of low-temperature printing and high-temperature printing to achieve quantitative customized and efficient production, the present invention has developed a method for printing at room temperature of 25°C to achieve stability while avoiding the influence of temperature on shape memory and mechanical properties. At the same time, based on the self-adhesive properties of the stent, it can be personalized and spliced into a variety of shapes for use, greatly broadening its application scenarios. In addition, the present invention mixes the active ingredient manganese dioxide with shape memory polyurethane to print a biomedical composite stent. At the same time, the printing method can also add other active ingredients, such as ferroferric oxide, magnesium metal, magnesium oxide, etc., to meet the different needs of existing biomedicine. The new biomedical stent and its manufacturing method are relatively simple in process, easy to industrialize and implement, and have a wide range of applicability.
[0075] Those skilled in the art can understand that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes can be made to them in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art can make their own changes and modifications without departing from the spirit and scope of the present application, so the scope of protection of the present application shall be based on the scope defined in the claims.
Claims
1. A biomedical stent, characterized in that: The biomedical stent comprises the following raw material components in percentage by mass: 96.0%-99.5% of shape memory polyurethane and 0.5%-4% of active particles; wherein the active particles comprise one or more of manganese dioxide, nano-magnesium oxide, ferroferric oxide and magnesium metal.
2. The biomedical stent according to claim 1, characterized in that: The biomedical scaffold comprises the following raw material components by mass percentage: 96.0% shape memory polyurethane and 4% manganese dioxide.
3. The method for preparing a biomedical scaffold according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: Prepare shape memory polyurethane, and stir and dissolve the shape memory polyurethane in a sealed environment at a temperature of 70-75° C. using dichloromethane as a solvent; After the shape memory polyurethane is completely dissolved and cooled to room temperature, active particles are added to obtain a mixed solution; Under open conditions, stirring at a temperature of 70-75° C. to volatilize the dichloromethane until the mixed solution becomes a non-flowing uniform colloid, thereby obtaining a shape memory polyurethane / active particle printing liquid; Printing is performed with the shape memory polyurethane / active particle printing liquid. After printing is completed, the dichloromethane is naturally volatilized to obtain a shape memory polyurethane / active particle composite bone repair scaffold with shape memory and self-adhesion functions, namely the biomedical scaffold.
4. The method for preparing a biomedical scaffold according to claim 3, characterized in that: The volume ratio of the shape memory polyurethane to dichloromethane is 1:7-1:10, preferably 1:
9.
5. The method for preparing a biomedical scaffold according to claim 3, characterized in that: In the step of preparing the shape memory polyurethane, stirring and dissolving the shape memory polyurethane in a sealed environment at a temperature of 70-75° C. using dichloromethane as a solvent, the stirring and dissolving is specifically dissolved by magnetic stirring, and the stirring time is 0.5-2 hours, preferably 1.5 hours.
6. The method for preparing a biomedical scaffold according to claim 3, characterized in that: After the shape memory polyurethane is completely dissolved and cooled to room temperature, active particles are added to obtain a mixed solution, which specifically includes cooling at room temperature for 1 hour until it is completely cooled to room temperature, and then adding active particles in an open condition.
7. The method for preparing a biomedical scaffold according to claim 3, characterized in that: The step of stirring at 70-75° C. in an open environment to evaporate the dichloromethane until the mixed solution becomes a non-flowing uniform colloid to obtain a shape memory polyurethane / active particle printing liquid specifically includes evaporating the mixed solution to 1 / 9 of its original volume.
8. The method for preparing a biomedical scaffold according to claim 3, characterized in that: The specific operating parameters for printing with the shape memory polyurethane / active particle printing liquid are: printing the shape memory polyurethane / active particle printing liquid at 25-28° C., 0.8 bar-1.1 bar extrusion, and a printing speed of 5-10 mm / s.
9. The method for using the biomedical stent according to claim 1 or 2, characterized in that: The method of use includes the following steps: The biomedical stent is placed under normal temperature conditions for deformation and compression treatment, and after the shape is fixed at normal temperature, the stent is implanted into a tissue site according to needs; At the corresponding temperature, with hot water at 45-60℃ or a wavelength of 808nm, the power density range is P = 0.5w / cm 2 -2 w / cm 2 By means of near-infrared light irradiation, the biomedical scaffold is restored to its original state, so as to fix the supporting tissue and promote tissue regeneration and repair; Alternatively, the biomedical scaffold is placed at room temperature, and scaffolds with different pore sizes, different active ingredients and different contents are spliced together according to the needs to customize the required shape, and placed in a temperature rise environment of 45-60°C or a wavelength of 808nm, with a power density range of P = 0.5w / cm 2 -2 w / cm 2 Under near-infrared light irradiation, the brackets are spliced into a whole due to their self-adhesion function.
10. Use of the biomedical stent according to claim 1 or 2 in the field of treating fractures and trauma.